PERSEPSI MAHASISWA PENDIDIKAN SEJARAH TERKAIT PEMBELAJARAN SEJARAH LOKAL DI PROGRAM STUDI PENDIDIKAN SEJARAH - Adnaninda, Adnaninda; Noor, Agus Sastrawan; Rahmatika, Ika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to determine the opinion of history education students to local history learning in the history education program at the FKIP Tanjungpura University. The method used is a survey method with qualitative research. The sources in this study was representatives of history education students who have taken local history courses and lecturers who support local history courses. Data collection techniques used were interview techniques, questionnaire techniques (Google forms), and documents. The results obtaining in this study are (1) students' perceptions to local historical material sources are quite good. Because, the source of the material using accord with the material presented. (2) learning planning is still not good enough. Because lecturer dosen’t make semester learning plans as he should. (3) Students' perceptions to the application of local history learning are not good. Because the lecturer doesn’t effective of lerning method, and he’s always conveys the same material in several meetings. (4) Students' perceptions regarding the evaluation of local history learning are quite good. Because the lecturer give assignments and conclusions individually at the end of the meeting. Keywords: Local History Learning, Historical Education Study Program, Student Perception